2018
DOI: 10.1093/biolre/ioy165
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic estrogen exposure recapitulates persistent ovarian transcriptional programs in a model of environmental endocrine disruption†

Abstract: Estrogens regulate key aspects of sexual determination and differentiation, and exposure to exogenous estrogens can alter ovarian development. Alligators inhabiting Lake Apopka, FL are historically exposed to estrogenic endocrine disrupting contaminants and are characterized by a suite of reproductive abnormalities, including altered ovarian gene expression and abated transcriptional responses to follicle stimulating hormone. Here, we test the hypothesis that disrupting estrogen signaling during gonadal differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 90 publications
1
9
0
Order By: Relevance
“…Animal Husbandry, Follicle-Stimulating Hormone Administration, and Sample Collection All experiments described herein were reviewed and approved by the institutional animal care and use committee at the Medical University of South Carolina (Charleston, SC), and alligator egg collections were approved and permitted by the Florida Fish and Wildlife Conservation Commission. The husbandry for animals used in this study has been previously described in detail (Galligan et al 2019;Hale et al 2019). Briefly, alligator eggs were collected shortly after oviposition from two sites in Florida, AP (Orange county, FL) and Lake Woodruff National Wildlife Refuge (WO; Volusia county, FL).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Animal Husbandry, Follicle-Stimulating Hormone Administration, and Sample Collection All experiments described herein were reviewed and approved by the institutional animal care and use committee at the Medical University of South Carolina (Charleston, SC), and alligator egg collections were approved and permitted by the Florida Fish and Wildlife Conservation Commission. The husbandry for animals used in this study has been previously described in detail (Galligan et al 2019;Hale et al 2019). Briefly, alligator eggs were collected shortly after oviposition from two sites in Florida, AP (Orange county, FL) and Lake Woodruff National Wildlife Refuge (WO; Volusia county, FL).…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that neonates were housed with similarly sized individuals, all animals were weighed and sorted by body mass every 2 wk. At 2 months of age, the animals were switched to a feeding schedule based on body mass to ensure relative homogeneity of animal size (Hale et al 2019). Briefly, animals weighing <92 g were fed daily, animals weighing 92-132 g were fed three times per week, and animals weighing >132 g were fed twice weekly.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dichlorodiphenyltrichloroethane (DDT) is a widespread and persistent organochlorine pesticide, and its primary metabolite, dichlorodiphenyldichloroethylene (DDE), is capable of disrupting androgen signaling (Kelce et al, 1995). Impaired reproductive function is associated with EDC exposure (including elevated levels of DDE) in a wild alligator population in Florida (Guillette et al, 1994(Guillette et al, , 1999, and experimental work has demonstrated that these alterations to reproductive function originate during development (Moore et al, 2012;Hale et al, 2019;Hale and Parrott, 2020). In laboratory studies, in ovo exposure to DDE induces female-biased sex ratios in turtles and alligators (Willingham and Crews, 1999;Milnes et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%